The Moderating Role of Business Strategy Deviation in Strengthening the Effect of Corporate Governance and Auditor Quality on Financial Reporting Quality - Septarini, Dina Fitri; Chandrarin, Grahita; Assih, Prihat (Journal of Cultural Analysis and Social Change, 2026)
This study examines the impact of corporate governance mechanisms (managerial ownership and institutional ownership) and auditor quality on financial reporting quality, with business strategy deviation as a moderating variable. Using a comprehensive sample of 60 manufacturing firms listed on the Indonesia Stock Exchange over the period 2019-2024, yielding 360 firm-year observations, we employ moderated regression analysis with panel data techniques. The findings reveal several noteworthy patterns. First, managerial ownership exhibits a positive but statistically insignificant direct effect on financial reporting quality (β = 0.012, p > 0.10), suggesting limited alignment effects (Morck et al., 1988; Holthausen et al., 1995) effects in Indonesia's concentrated ownership environment. Second, institutional ownership demonstrates no significant relationship with reporting quality (β = -0.003, p > 0.10), reflecting institutional investor heterogeneity in emerging markets. Third, auditor quality shows a robust positive influence on reporting quality (β = 0.087, p < 0.01), demonstrating the effectiveness of external monitoring across institutional contexts. Most notably, business strategy deviation significantly moderates the relationship between managerial ownership and financial reporting quality (β = 0.034, p < 0.05), suggesting that strategic deviations from industry norms amplify the importance of insider alignment effects (Morck et al., 1988; Holthausen et al., 1995) in ensuring reporting credibility. However, the moderating effects on institutional ownership and auditor quality relationships remain insignificant. These results contribute to agency theory by highlighting the contextual nature of governance effectiveness and provide practical implications for regulators seeking to enhance financial reporting quality in emerging markets.